MULTI-DAY INFUSION OF AUTOLOGOUS CRYOPRESERVED PERIPHERAL BLOOD PROGENITOR CELLS IN PATIENTS WITH HEMATOLOGICAL MALIGNANCIES -TNE INFLUENCE ON ENGRAFTMENT TOXICITY - Pivkova Veljanovska, Aleksandra; Cevreska, Lidija; Siljanoski, Nikola; Karanfilski, Oliver; Genadieva Stavrikj, Sonja; Stojanoski, Zlate; Panovska Stavridis, Irina; Krstevska balkanov, Svetlana; Trajkova, Sanja; Georgievski, Borche (My University, 2005)
Peripheral blood progenitor cells (PBPC) are increasingly used as source of stem cells in both autologous and allogeneic settings for patients with hematological malignancies. Based on previously non-randomized studies for enhanced engraftment during multi-day infusion of cryopreserved PBPC in the autologous transplantation, some transplant centers infuse harvests over 3 days. To evaluate the benefit of fractionated infusions of PBPC we included 37 patients with hematological malignancies (AML 11, NHL 9, HD 9, MM 6, ALL 2) treated with high-dose chemotherapy (HD1) followed by autologous stem cell trans· plantation (ASC1) at Department of hematology, Skopje, Macedonia. The patients were randomized to receive cryopreserved PBPC concentrates divided over 1,2 or more than 3 days. PBPC were mobilized with high-dose VPI6 2g/m' for AML patients, intermediate-dose cyclophosphamide 1-2 g/m' for lymphoproliferative malignancies and/or G-CSF 5microgrlkg alone. PBPC concentrates were cryopreserved with 5% DMSO solutions using controlled rate freezing procedures (Nicole plus PC Espace 330. Patients received daily G-CSF 10microgr/kg i,v over 30 min beginning 4h after the infusion of the first aliquot of PBPCs. The median amount of infused PBPC solution was 430 ml (240- 780ml). Engraftment was registered for Ne>0.5xl <Y/L on day + 10 (8- 14) and for Plt>20xl0'1L on day + 13 (8-20) with no sasystical difference between groups that received I, 2 or more than 3 days infusions of PBPCs. Transfusion requirements were for Er 2 doses (0-4) and Plt 14 doses (O-33). The statistical data revealed that infusion related toxicity was similar for all groups of patients. At the end we can conclude that multi-day infusion of PBPC harvests does not influence the engraftment or reduce toxicity.